Revisión de los procesos para la producción de combustibles provenientes de residuos plásticos. (2021)
Currently the generation of solid waste is one of the greatest environmental problems that directly refers to the environment and humanity. Due to the composition of the plastic, it is an element that makes it resistant to any type of treatment to be degraded. Due to this, when the plastic becomes 7 residual and there is not a good management and a good handling brings with it serious consequences for the environment and for human health. This problem is increasing day by day due to not having an adequate recycling system and good management with this type of plastics. Therefore, work must be done to implement new, innovative, effective and viable methodologies that are friendly to the environment in order to provide a possible solution to the environment, and in the same way take advantage of this type of material to generate energy. However, there are several methodologies for the treatment of plastic waste, in this monograph we are going to focus on one of these processes, which is effective to mitigate this type of contamination and is also of great importance, since as a result it generates fuel from plastic.